PELAKSANAAN SOSIALISASI DAN EDUKASI PENCEGAHAN PROGRESIVITAS HIPERTENSI PADA LANSIA DI DESA SARIMULYO - Berta Arwi Yunita; Adnan Faris Naufal (Universitas Majalengka, 2022)
Background: Hypertension is a condition characterized by persistent high blood pressure in systemic arteries, namely systolic 140 mmHg and/or diastolic 90 mmHg. In connection with that, there are many risk factors for hypertension, including age. In Indonesia, the number of elderly people continued to grow, with most of them suffered from hypertension. Knowledge about hypertension that is still lacking made the number of people with hypertension more and more. In addition, one of the risk factors that can be changed is physical activity. The low level of physical activity made many elderly who suffered from hypertension experienced high hypertension progression. From this socialization activity, participants in the socialization could find out about hypertension in general and exercises that could prevent the progression of hypertension. Objective: to increase the level of public knowledge about hypertension and how to prevent the progression of hypertension in the elderly in Sarimulyo village. Methods: socialization and education. Result: after the socialization session finished, participants already knew at least what hypertension is, in general, the symptoms that arise when suffering from hypertension, and know what exercises are easy to do to keep blood pressure normal. Conclusion: there is an increase in the understanding of the elderly about hypertension in general, the symptoms or signs of hypertension and physical exercise that can help them to prevent the progression of hypertension.